Unintended effects of human actions, or the reforms of the higher education system - Jelonek, Magdalena (Journal of Public Governance, 2013)
The author discusses the thesis presented in J. Hausner’s and J. Górniak’s papers published in this volume. The author presents her own perspective on the process of solving the dilemmas of freedom/determinism of human action, complexity of the social world, limitations of sociological theory, and co-creating social reality in the process of knowledge production. The examples illustrating her ideas come from the field of sociology of education, and they are mostly related to the higher education system reform. The author raises two practical questions, one regarding cognition (Is it possible to design policies based on evidence in the area of higher education?), and the other focussed on action (Is it possible to implement effectively any educational policies, including equality policies, given that, so far, most educational reforms (in this area) have ended in a more or less spectacular disaster?